2016
DOI: 10.18192/uojm.v6i2.1811
|View full text |Cite
|
Sign up to set email alerts
|

The borders that remain: prevention of cervical cancer in refugee and immigrant women in Canada

Abstract: Objectives: Cancer of the uterine cervix is primarily caused by infection of human papillomavirus (HPV), and annually results in the deaths of 266,000 women worldwide. Screening for cervical cancer, predominantly via Papanicolau (Pap) tests, has tremendously reduced cervical cancer morbidity and mortality in many developed countries, Canada included. Vaccination against HPV also shows great potential as a preventative measure. Unfortunately, refugee and recently immigrated women are among the least likely to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…We used multivariable logistic regression models to estimate the association between refugee category (our primary exposure of interest), and the two outcomes of interest: CCS test completion (primary outcome) and CCS test offered (secondary outcome), while accounting for important sociodemographic and clinical factors which were included in the models as covariates [ 26 , 27 ]. We calculated odds ratios for the outcomes of interest using GARs as the reference group, as they were the largest group (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used multivariable logistic regression models to estimate the association between refugee category (our primary exposure of interest), and the two outcomes of interest: CCS test completion (primary outcome) and CCS test offered (secondary outcome), while accounting for important sociodemographic and clinical factors which were included in the models as covariates [ 26 , 27 ]. We calculated odds ratios for the outcomes of interest using GARs as the reference group, as they were the largest group (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…As multidisciplinary clinics, they aim to reduce barriers, provide free or low-cost and comprehensive care with cultural humility, despite clinical complexity. However, while some studies recommend these dedicated clinics, limited evidence exists to show if these clinics do improve preventative care such as CCS for this vulnerable population, especially amidst major health policy changes such as the IFHP cuts [ 16 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Refugees and immigrants are often of low education and income. Language and cultural barriers can result in lack of knowledge and understanding of preventative procedures, and, especially when coinciding with past trauma, can result in fear authoritative physician with whom they would likely struggle to communicate (Beckett, 2016). Important factors are also older ages and recent entry into host county.…”
Section: Cervical Cancermentioning
confidence: 99%
“…Meta-analysis assessing the burden of cervical HPV infection among more than one million women without cervical disease showed that 11.7 of the women worldwide are positive for HPV DNA (Bruni et al, 2010). The prevalence of high risk HPV ranges from 11 in healthy women in Belgium, 20 in female university students in the USA to 46 in Spanish women in prisons (Beckett, 2016). Study from 2010 shows that 59.2 of Slovenian women in life have been infected (they have genotypically specific antibodies in the blood) with at least one of the 12 high-risk HPV genotypes and that at the time of the study, in 12.2  of women HPV genotype was proven in a cervical smear (Komloš et al, 2011).…”
Section: Prevalence Of Hpv Infectionmentioning
confidence: 99%
“…Access to health services is one of the significant challenges that many immigrant women face in Canada during their cancer care. [2][3][4] Low socioeconomic status, low levels of education, and language are the main reasons that complicate immigrant women's ability to access health services. [5] The availability of interpreters is also considered a barrier to access to health services.…”
Section: Introductionmentioning
confidence: 99%